Cover Image, Volume 30, Issue 5. (May 2017) - Deniz, Cem M.; Carluccio, Giuseppe; Collins, Christopher
Abstract : The cover image, by Cem M. Deniz et al., is based on the Research Article Parallel transmission RF pulse design with strict temperature constraints, DOI:10.1002/nbm.3694 .